2x + 3 = -2x + 39 x = 9 | 6x - 27 = x + 8 x = 7 |
9x + 5 = x + 69 x = 8 | -3x + 3 = -2x - 3 x = 6 |
3x + 20 = -5x - 4 x = -3 | -5x + 13 = 3x - 3 x = 2 |
5x + 9 = 4x + 9 x = 0 | x - 5 = 2x - 10 x = 5 |
-7x - 9 = 5x - 9 x = 0 | x + 28 = 4x + 1 x = 9 |
7x - 23 = 2x - 8 x = 3 | 8x + 9 = 9x + 16 x = -7 |
9x - 3 = 4x - 3 x = 0 | 9x + 8 = 10x + 1 x = 7 |
-2x - 28 = -4x - 8 x = 10 | 4x - 7 = 6x - 27 x = 10 |
-3x + 58 = 7x + 8 x = 5 | -5x - 31 = -2x - 7 x = -8 |
7x + 5 = 4x + 11 x = 2 | 9x + 26 = 5x - 10 x = -9 |